2014
DOI: 10.1113/jphysiol.2013.268136
|View full text |Cite
|
Sign up to set email alerts
|

P2Y1 receptor‐mediated potentiation of inspiratory motor output in neonatal rat in vitro

Abstract: Key pointsr The role of metabotropic purinergic receptors (P2YRs) in modulating motor output from the CNS is virtually unknown, despite the fact that many motoneurons, including respiratory motoneurons, express P2YRs.r Using rhythmically active brainstem-spinal cord and medullary slice preparations, we demonstrate that compared to the 4th cervical spinal nerve (C4) inspiratory output controlling the diaphragm, P2YR activation is >10 times more efficacious at potentiating the hypoglossal nerve (XII) inspiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 119 publications
(188 reference statements)
3
26
0
4
Order By: Relevance
“…Therefore, we believe that ATP will be involved in the following chain of events: carotid body activation by low levels of O2 stimulates carotid sinus nerve terminals by sending information to the second-order neurons into the NTS; these second-order neurons will activate the respiratory neurons located in the ventral respiratory group (Alvares et al, 2014. We also showed that the P2Y1 blocker did not change the ventilatory response to hypoxia in awake unrestrained rats.…”
Section: Contribution Of Purinergic Signaling Into the Rtn During Hypmentioning
confidence: 70%
See 4 more Smart Citations
“…Therefore, we believe that ATP will be involved in the following chain of events: carotid body activation by low levels of O2 stimulates carotid sinus nerve terminals by sending information to the second-order neurons into the NTS; these second-order neurons will activate the respiratory neurons located in the ventral respiratory group (Alvares et al, 2014. We also showed that the P2Y1 blocker did not change the ventilatory response to hypoxia in awake unrestrained rats.…”
Section: Contribution Of Purinergic Signaling Into the Rtn During Hypmentioning
confidence: 70%
“…Há evidências emergentes de que os astrócitos são a fonte do componente purinérgico para os neurônios quimiossensíveis do RTN qual reduziu a resposta respiratória frente à hipóxia . Ainda, outros estudos mostram a participação purinérgica na coluna respiratória dorsal e ventral durante a hipóxia (ALVARES et al, 2014;BRACCIALLI et al, 2008;FUNK et al, 2015); no entanto pouco se sabe especificamente da participação do componente purinérgico no RTN no quimiorreflexo periférico. Após a cirurgia encefálica, os ratos receberam uma injeção intramuscular (0,2 ml/rato) de Pentabiótico Veterinário -Pequeno Porte (Fort Dodge Saúde Animal Ltda.)…”
Section: Sinalização Purinérgica No Núcleo Retrotrapezóideunclassified
See 3 more Smart Citations